Pengaruh Model RADEC dengan Pendekatan STEM Terhadap Keterampilan Komunikasi - Berlian Priskanovita (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study was conducted to examine the effect of the RADEC model with a STEM approach on students’ communication skills. The research involved 30 fifth-grade students at SDN Mayangan 01 during the even semester of the 2025/2026 academic year. The method used was a quasi-experimental design with a nonequivalent control group design. The research instrument consisted of observation sheets developed based on OSPI indicators (Chambers, 2012), implemented through pretest and posttest observations. Data analysis included normality testing, homogeneity testing, and hypothesis testing using the Independent Sample T Test with the assistance of SPSS. The results showed a significant difference between the experimental class and the control class (0,000 < 0.05). These findings indicate that the RADEC model with a STEM approach has an effect on improving students’ communication skills. It is recommended that this study can serve as a reference in developing learning strategies or media, particularly in helping students explain scientific terms to their peers using simpler language.
The Effect of the RADEC Learning Model with the STEM Approach on Communication Skills
Approved by Teddy
Keywords: Communication; RADEC; Science; STEM